LE UNITA' STRATIGRAFICHE APTIANO-MAASTRICHTIANE DELLE PREALPI BERGAMASCHE (Rivista italiana di Paleontologia e Stratigrafia, 2023)
This report deals with the Cretaceous sequence which overlies the "Maiolica" formation in che Bergamo area (Lombardian Basin, Northern ltaly). The sequence. mainly terrigenous, testifies a contemporaneous tectonic activity both at a locai as were regional scale. Between Aptian and Turonian at least, the facies discribucion suggcscs almost the same paleogeographic sctting as during the Jurassic. Some elevated areas bounded by normai rejuvenated faults are observed, which are M. Cavallo, M. Misma and the Zandobbio hills, oricntcd as "Giudicarie" trcnds. The first tcrrigenous turbiditcs are Aptian in age; but it is during the Cenomanian till to thc Turonian that the supply of clastic materiai develops and progrades from Centrai Bergamo arca toward the west. Strong mass movcments havc becn documcnted ali around the aforementioned elevated areas. The Aptian to Turonian turbidites are possibly linkcd to the paleoalpine compressive orogenic phases of the Eastern and Centrai Alps. The arenaceous turbidites Coniacian in age, are supposed to originate from rcscdimentation of "Gosau Molasse" sliding into the Lombardian Basin through the "Giudicarie" structural pattern. The clastic supply as well as subsidence were so strong that the originai paleogeographic setting was completely drowned. The calcarenitic turbidites as well as the silicoclastic ones which caractcrize the "Pietra di Credaro" and the "Bergamo Flysch" respectively, are thoughc to come from differenc areas, during thc time span elapsed between Santonian and Campanian.